Liturgical language and the formation of reflectively embodied imagination as exemplified in the doxological poetry of Ephrem the Syrian - Edie, Fred P. (International journal of Christianity & education, 2016)
Christian Catechumens of antiquity participated bodily in a variety of deeply evocative ritual symbolic practices. At the Syrian church where Ephrem served as a deacon, they would also have spoken or sung poetic verse juxtaposing images from the biblical story to symbols and practices of the baptismal rites of initiation. Although Ephrem's aim was primarily doxological, it also formed in participants a reflective Christian imagination, one that overlaps with but is not identical to contemporary accounts of an embodied imaginative habitus. Christians in the present day who learn to imagine like Ephrem will grow in their capacity to see God's saving work grounded in and through seemingly ordinary experience, they will be challenged to dwell humbly in the mystery of God's revelation, and they will cultivate resources and poetic license for discerning, naming, and participating in God's coming Kingdom.